Distributions of Ni in MCM-41 for the hydrogenation of N-ethylcarbazole. (15th September 2022) - Chen, Ben; Hui, Bowen; Dong, Yuting; Sheng, Qiang; Li, Xiang; Hao, Qinglan; Liu, Chunjing
Graphical abstract: Highlight: Ni particles were located both in the pores and on the surface of Ni/MCM-41. The reduction of Ni particles in the pores of MCM-41 required higher temperature. The electron density of Ni particles in Ni/MCM-41 was lower than those in Ni/SiO2 . The surface Ni particles were more active than those in the pores of MCM-41. The selectivity to dodecahydro product increased with the electron density of Ni. Abstract: The SiO2 - and MCM-41-supported Ni catalysts were prepared by an incipient wetness impregnation method and their performance in the hydrogenation of liquid organic hydrogen carrier were evaluated using N-ethylcarbazole (NEC) as model compound. Ni particles were mainly located on the external surface of the SiO2 -supported Ni catalysts. Both Ni particles on the external surface and filled in the mesopores of MCM-41 were found in the MCM-41-supported catalysts. The reduction of surface Ni particles occurred at low temperature (ca. 365 °C), but the complete reduction of Ni particles in the mesopores of MCM-41 required high temperature (ca. 555 °C). The MCM-41-supported Ni particles possessed lower electron densities than the SiO2 -supported ones. The surface Ni particles showed the same activity in the hydrogenation of NEC, which were more active than those in the mesopores of MCM-41. A correlation between the electron density of Ni particles and their selectivity was observed. The higher the electron density of Ni particles, the higher the selectivity to the fully hydrogenated product (dodecahydro-N-ethylcarbazole) is.